Vulnerability and protection of glass windows under blast: experiments, methods and current trends - Zhang, Xihong; Bedon, C. (2017)
Glass has been overwhelmingly used for windows and facades for modern constructions. Nevertheless, due to its relatively low tensile strength and mostly brittle behaviour, compared to other structural members, glass windows/facades are one of the most fragile components for a building envelop that are always associated with vast casualties in a blast incident. Several researches have been carried out to study the performance of glass windows and facades under blast loading, which include laboratory investigations on glass dynamic properties; analytical solutions for the analysis of the response of monolithic and laminated glass panes under shock; numerical modelling of window vulnerability to air blast waves; laboratory or field blast tests to validate the prediction and performance of glass windows and assemblies, as well as the efficiency of possible mitigation and retrofitting solutions for novel or existing glass claddings. This paper presents a review on the state of art of analysis and design of glass window/facade system under blast loading, with evidence of available experimental outcomes, design methods and trends, open challenges